O ensino de inglês em curso superior de hotelaria: um estudo sobre práticas docentes - Simões, Renata Mendes (2010)
The main focus of this qualitative study is the analysis of pedagogical practices of teachers of English as a second language in the undergraduate course of Hospitality Management. The subject matter of this study is as follows: How is the teaching of English for hospitality management students characterized according to their teachers? Two of the most highly regarded post-secondary institutions of Sao Paulo were chosen for the execution of this study, for they are considered by the market as the main educators of professionals for this area. The theoretical framework of this research is based on scholars who are engaged with studies related to learning and to the professional development of teachers. Among others, we can mention Masetto (1998, 2003), Mizukami (1986), Vasconcelos (2000), Freire (2004), Perrenoud (2002), e Shulman (2004). The data for this study were collected through interviews with English teachers. For the analysis and interpretation of the teachers discourses, three main points were considered: (a) academic education, (b) professional performance and (c) students learning. Such discourses indicate how university level English teachers verbalize the construction of their teaching practices. The results show that although the teachers have different teaching time experience and different age, they share some of the same references and origins, and these references influence their practices. Each and every one of them has their own teaching experience and they believe this facilitates their teaching practice. They also indicate that, along their professional journey, they construct knowledge about how to teach English to professionals with specific profiles.